Sjogren's syndrome: A review - Mallika Kishore; Sunil Ramchandra Panat; Ashish Aggarwal; Nupur Agarwal; Nitin Upadhyay; Ritika Garg (Wolters Kluwer Medknow Publications, 2014)
Sjogren's syndrome (SS) is a chronic autoimmune disease characterized by the lymphocytic infiltration of salivary and lacrimal glands leading to xerostomia and keratoconjunctivitis sicca. Prevalence of primary SS in the general population has been estimated to be around 1-3%. SS is an under-recognized disease in which most of the significant progress has been made in the past 25 years. The herald of newer diagnostic tools could help clinicians and thereby provide significant relief to patients through earlier treatments. The treatment of SS is limited to symptomatic management, and involves the use of solutions to replace salivary secretion and afford a measure of hydration. The purpose of present paper is to highlight the difficulties and complexities that are inherent in the diagnosis of SS and the important role that dental practitioners can play in the management of its oral manifestations.